Plant Factories Are Heating Up: Hunting for the Best Combination of Light Intensity, Air Temperature and Root-Zone Temperature in Lettuce Production - Carotti, Laura; Graamans, Luuk; Puksic, Federico; Butturini, Michele; Meinen, Esther; Heuvelink, Ep; Stanghellini, Cecilia (Frontiers in Plant Science, 2021)
This study analyzed interactions among photon flux density (PPFD), air temperature, root-zone temperature for growth of lettuce with non-limiting water, nutrient and CO2 concentration. We measured growth parameters in 48 combinations of a PPFD of 200, 400 and 750 µmol m-2 s-1 (16 h daylength), with air and root-zone temperatures of 20, 24, 28 and 32°C. Lettuce (Lactuca sativa cv. Batavia Othilie) was grown for four cycles (29 days after transplanting). Eight combinations with low root-zone (20 and 24°C), high air temperature (28°C and 32°C) and high PPFD (400 and 750 µmol m-2 s-1) resulted in an excessive incidence of tip-burn and were not included in further analysis. Dry mass increased with increasing photon flux to a PPFD of 750 µmol m-2 s 1. The photon conversion efficiency (both dry and fresh weight) decreased with increasing photon flux: 29, 27 and 21 g FW shoot and 1.01, 0.87 and 0.76 g DW shoot per mol incident light at 200, 400 and 750 μmol m-2 s-1, respectively, averaged over all temperature combinations, following a concurrent decrease in specific leaf area (SLA). The highest efficiency was achieved at 200 μmol m-2 s-1, 24°C air temperature and 28°C root-zone temperature: 44 g FW and 1.23 g DW per mol incident light. The effect of air temperature on fresh yield was linked to all leaf expansion processes. SLA, shoot mass allocation and water content of leaves showed the same trend for air temperature with a maximum around 24°C. The effect of root temperature was less prominent with an optimum around 28°C in nearly all conditions. With this combination of temperatures, market size (fresh weight shoot = 250g) was achieved in 26, 20 and 18 days, at 200, 400 and 750 μmol m-2 s-1, respectively, with a corresponding shoot dry matter content of 2.6, 3.8 and 4.2%. In conclusion, three factors determine the “optimal” PPFD: capital and operational costs of light intensity vs the value of reducing cropping time, and the market value of higher dry matter contents.